Elevation in serum uric acid levels predicts favourable response to erlotinib treatment in patients with metastatic non‐small‐cell lung cancer. (28th November 2019) - Selcukbiricik, Fatih; Ozdogan, Elif; Dagel, Tuncay; Tanju, Serhan; Erus, Suat; Ertuglu, Lale A.; Kapdağlı, Murat; Tural, Deniz; Bilici, Ahmet; Dilege, Sukru; Mandel, Nil M.; Kanbay, Mehmet
Abstract: What is known and objective: Erlotinib is a small molecule tyrosine kinase inhibitor which blocks the activation of epidermal growth factor receptor (EGFR), a transmembrane receptor that is upregulated in many cancer types. Inhibition of angiogenesis with consequent impairments in intratumoral microcirculation is one of the mechanisms through which EGFR inhibition halts the progression of cancer. A consequence of impaired microcirculation is intratumoral hypoxia, which results in increases in serum uric acid levels. The goal of this study was to investigate the relationship between serum uric acid levels and response to erlotinib in metastatic non‐small‐cell lung cancer (NSCLC). Methods: A total of 56 patients with metastatic non‐small‐cell lung cancer who received erlotinib for a duration of at least 3 months were included in this retrospective cohort study. Demographic characteristics, progression status, baseline serum uric levels and 3‐month serum uric acid levels were recorded and analysed. Results and discussion: Of the study population, 21 (37.5%) were female and 35 (62.5%) were male patients. No significant difference in above demographic characteristics was observed among exitus, survivor with progression and survivor without progression groups. Patients who responded favourably to erlotinib with no progression of their disease had significantly increased uric acid levels at 3‐month follow‐up ( P  = .01). Such a correlation was not observed if the patient was exitus ( P  = .47) or had progressed on erlotinib therapy ( P  = .19). What is new and conclusion: In conclusion, this study is the first to demonstrate significant increases in serum uric acid levels in patients with metastatic NSCLC who responded favourably to erlotinib and had no progression under erlotinib therapy. Further studies are required to confirm and characterize serum uric acid as a novel biomarker in predicting the outcome in those with metastatic NSCLC. Abstract : Serum uric acid levels in patients with metastatic non‐small‐cell lung cancer (NSCLC) who responded favourably to erlotinib and had no progression under erlotinib therapy. Uric acid may be as a novel biomarker in predicting the outcome in those with metastatic NSCLC.